Soil protection by winter‑cycle cover crops in South Brazil - Ziech, Ana Regina Dahlem; Conceição, Paulo Cesar; Luchese, Augusto Vaghetti; Balin, Nilson Marcos; Candiotto, Gilvanei; Garmus, Taís Gabriele (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the potential of winter‑cycle cover crops on the protection of soil, in the southwest region of the state of Paraná, in Southern Brazil, as affected by coverage rate, dry matter (DM) production, C/N ratio, and maintenance of remaining DM of vegetable residues on soil surface. The following were used as cover crops: black oat (Avena strigosa), annual ryegrass (Lolium multiflorum), rye (Secale cereale), white lupine (Lupinus albus), common vetch (Vicia sativa), wild radish (Raphanus sativus), and consortia between black oat + common vetch (O+V) and black oat + common vetch + wild radish (O+V+R). The experiment was evaluated during the 2010/2011 and 2011/2012 growing seasons. Plant decomposition was determined with the use of litter bags. Black oat and the consortia provided higher rates of soil coverage at the first 50 days after sowing, with DM production higher than 2,600 kg ha-1 on soil surface. The consortia between O+V+R had a balanced C/N ratio and intermediate decomposition in relation to single cropping, promoting 1,045 kg ha-1 residue on soil surface, 120 days after its management. Forage grasses alone and consortia with forage grasses show higher soil protection potential.